The Impact of Public Deliberation on Climate Change Opinions Among U.S. Citizens - Ghimire, Rajiv; Anbar, Nathaniel; Chhetri, Netra B. (Frontiers in Political Science, 2021)
Governance of climate change has become a major global environmental issue in the 21st century, and in the absence of wider citizen engagement poses risks of global proportions. Much of the current climate governance debate, unfortunately, is limited to scientists, politicians, and interest groups. With few exceptions, everyday citizens are spectators at best, their views, if not absent, are dismally represented in policy processes. To close the widening gap between citizens and policymakers, thereby increasing the sense of ownership of environmental policies by ordinary people, several methods of citizen engagement for global environmental governance have emerged. The effectiveness of these methods, however, relies upon the ability of citizens to deliberate meaningfully, especially in issues such as climate change. We conducted a study in conjunction with World Wide Views on Climate and Energy, a global citizen consultation that aims to solicit carefully considered public views on pressing issues, to determine whether American citizens are receptive to deliberation, and to ascertain what effect it had on their opinions, if any, could be observed. Along with the descriptive analysis, we performed a non-parametric Wilcoxon signed-rank test of selected pre-and post-event opinions of the participants from the US. Our study revealed that providing US citizens with the opportunity to engage in deliberation resulted in increased awareness regarding climate change and greater trust in science, technology, and international agreements. The change in opinion was more pronounced among people whose political orientation titled to the right or who considered themselves as neutral. Citizen’s opinions, especially after the event, resulted in less polarized views towards the global consensus on climate change. This finding suggests that US citizens are receptive to scientific information if it is communicated in an appropriate manner – a characteristic necessary for the creation of deliberative democratic governance on socially contested issues.